Recent Advances in the Molecular Design and Delivery Technology of mRNA for Vaccination Against Infectious Diseases - Yang, Lu; Tang, Lin; Zhang, Ming; Liu, Chaoyong (Frontiers in Immunology, 2022)
Vaccines can prevent many millions of illnesses against infectious diseases and save numerous lives every year. However, traditional vaccines such as inactivated viral and live attenuated vaccines cannot adapt to emerging pandemics due to their time-consuming development. With the global outbreak of the COVID-19 epidemic, the virus continues to evolve and mutate, producing mutants with enhanced transmissibility and virulence; the rapid development of vaccines against such emerging global pandemics becomes more and more critical. In recent years, mRNA vaccines have been of significant interest in combating emerging infectious diseases due to their rapid development and large-scale production advantages. However, their development still suffers from many hurdles such as their safety, cellular delivery, uptake, and response to their manufacturing, logistics, and storage. More efforts are still required to optimize the molecular designs of mRNA molecules with increased protein expression and enhanced structural stability. In addition, a variety of delivery systems are also needed to achieve effective delivery of vaccines. In this review, we highlight the advances in mRNA vaccines against various infectious diseases and discuss the molecular design principles and delivery systems of associated mRNA vaccines. The current state of the clinical application of mRNA vaccine pipelines against various infectious diseases and the challenge, safety, and protective effect of associated vaccines are also discussed.